Concentrations of plasma free palmitoleic and dihomo-gamma linoleic fatty acids are higher in children with abdominal obesity (2018)
ABSTRACT: Increased plasma free fatty acids (FFAs) are associated with cardiometabolic risk factors in adults with abdominal obesity (AO). However, this association remains controversial in children. This study analyzed plasma FFA concentration in children with and without AO. Twenty-nine children classified with AO were matched by age and sex with 29 non-obese individuals. Blood samples were collected after fasting for 10–12 h. Plasma concentration of glucose, insulin, triglycerides, total cholesterol, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were determined by automatized methods. FFAs were analyzed by gas chromatography. Children with and without AO had similar age (7.1 ± 2.6 vs. 7.2 ± 2.7 years; p > 0.05) but obese children showed higher (p < 0.05) body mass index (BMI) (+4.3 kg/m2), systolic blood pressure (+5.1 mmHg), and insulin (+27.8 pmol/L). There were no significant differences in plasma total FFA concentration between groups (1.02 ± 0.61 vs. 0.89 ± 0.37 mmol/L; p > 0.05). However, children with AO had higher palmitoleic acid (0.94 vs. 0.70 wt %; p < 0.05) and dihomo-gamma linoleic acid (DHGL) (2.76 vs. 2.07 wt %; p < 0.05). Palmitoleic and DHGL acids correlated (p < 0.05) with BMI (r = 0.397; r = 0.296, respectively) and with waist circumference (r = 0.380; r = 0.276, respectively). Palmitoleic acid correlated positively with systolic blood pressure (r = 0.386; p < 0.05) and negatively with HDL-C (−0.572; p < 0.01). In summary, children with AO have higher plasmatic concentrations of free palmitoleic and DHGL fatty acids, which correlate with cardiometabolic risk factors.